Towards an assessment of the ATLAS data on the branching ratio Γ(Λ0b→ψ(2S)Λ0)/Γ(Λ0b→J/ψΛ0) - Gutsche Th. Thomas; Ivanov M. A. Mikhail Alekseevich; Korner J. G. Jurgen; Santorelli P. Pietro; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2015, 2015)
Title screen